Implementing the precautionary principle: Perspectives and prospects - Fisher, E; Jones, J; von Schomberg, R (Edward Elgar Publishing Ltd., 2006)
'. . . this book represents a welcome addition to the literature on PP and is recommended for readers interested in risk assessment, decision making and the precautionary principle.' © Elizabeth Fisher, Judith Jones and René von Schomberg, 2006. All rights reserved.